Conflicto entre equipo médico y padres en decisiones de limitación de esfuerzo terapéutico que afectan a menores de edad (el caso de Andrea L.O.) (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
This paper analyzes the cases of limitation of therapeutic effort regarding minors when there is a conflict between the medical team and the legal representatives. In this regard, it describes the complex legal framework for this matter under Spanish law and analyzes and assess the legal issues that Andrea's case raises.
Keywords: Euthanasia; Euthanasia; Informed Consent; Informed Consent; Patient's Right to Make Decisions at the End of his Life; Patient's Right to Make Decisions at the End of his Life; Consent by Legal Representation; Consent by Legal Representation; Minors; Minors; Conflict Between Medical Judgment and Legal Representatives; Conflict Between Medical Judgment and Legal Representatives.